2016
DOI: 10.14202/vetworld.2016.717-722
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of titers of anti-Brucella antibodies of naturally infected and healthy vaccinated cattle by standard tube agglutination test, microtiter plate agglutination test, indirect hemagglutination assay, and indirect enzyme-linked immunosorbent assay

Abstract: Aim:We determined the antibody response in cattle naturally infected with brucellosis and normal healthy adult cattle vaccinated during calf hood with strain 19.Materials and Methods:The antibody titers were measured by standard tube agglutination test (STAT), microtiter plate agglutination test (MAT), indirect hemagglutination assay (IHA), and indirect enzyme-linked immunosorbent assay (iELISA) as per standard protocols.Results:The mean STAT titers were 1.963±0.345 in infected cattle and 1.200±0.155 in health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
(17 reference statements)
1
6
0
Order By: Relevance
“…RBT showed no antibody found before vaccination, as no agglutination was observed. Vaccinated calves showed positive RBT, similar to the results of other workers (Afzal et al, 2000;Mohan et al, 2016;Poesteret al, 1998).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…RBT showed no antibody found before vaccination, as no agglutination was observed. Vaccinated calves showed positive RBT, similar to the results of other workers (Afzal et al, 2000;Mohan et al, 2016;Poesteret al, 1998).…”
Section: Resultssupporting
confidence: 90%
“…The disease also infects humans. About 50,000 cases of human brucellosis are reported every year globally (Mohan et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported earlier (Mohan et al, 2016) that infected animals have very high titers of antibodies compared to the vaccinated animals. However, in the absence of an assay for differentiation of infected from vaccinated animals (DIVA assay), it is not possible to determine whether these antibodies are protective or not and are induced by the vaccine or due to response of the animal to acute infection and whether they are of any relevance to prognosis.…”
Section: Resultsmentioning
confidence: 84%
“…Wang et al ( 2015 ) developed a highly advanced version of a monoclonal antibody-based cELISA against LPS for the diagnosis of bovine brucellosis, which revealed higher specificity than the commercially available cELISAs and RBPT (Ahmed et al 2011 ; Kirit et al 2017 ). The analysis of the anti- Brucella antibody titers of naturally infected and vaccinated cattle by indirect ELISA, SAT, indirect hemagglutination assay and microtiter plate agglutination test revealed that the naturally infected animals presented much higher titers of agglutinating antibodies in comparison to the healthy vaccinated cattle (Mohan et al 2016 ).…”
Section: Diagnosismentioning
confidence: 99%